Frictional Characteristics of Atomically Thin Sheets - Lee, Changgu; Li, Qunyang; Kalb, William; Liu, Xin-Zhou; Berger, Helmuth; Carpick, Robert W; Hone, James (Science (American Association for the Advancement of Science), 2010)
Using friction force microscopy, we compared the nanoscale frictional characteristics of atomically thin sheets of graphene, molybdenum disulfide (MoS₂), niobium diselenide, and hexagonal boron nitride exfoliated onto a weakly adherent substrate (silicon oxide) to those of their bulk counterparts. Measurements down to single atomic sheets revealed that friction monotonically increased as the number of layers decreased for all four materials. Suspended graphene membranes showed the same trend, but binding the graphene strongly to a mica surface suppressed the trend. Tip-sample adhesion forces were indistinguishable for all thicknesses and substrate arrangements. Both graphene and MoS₂ exhibited atomic lattice stick-slip friction, with the thinnest sheets possessing a sliding-length-dependent increase in static friction. These observations, coupled with finite element modeling, suggest that the trend arises from the thinner sheets' increased susceptibility to out-of-plane elastic deformation. The generality of the results indicates that this may be a universal characteristic of nanoscale friction for atomically thin materials weakly bound to substrates.